Pemberdayaan Ibu Balita dalam Pencegah Stunting : Kelurahan Kampung Jawa, Kota Solok - Tintin Sumarni; Gusnedi; Deharnita; Aini Yusra; Firwandri Marza; Abdul Gafar (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
This community service aimed to increase the knowledge and awareness of mothers of toddlers in preventing stunting in Kampung Jawa Village, Solok City. The activity was conducted on August 26, 2025, targeting mothers of toddlers, health workers, cadres, and community leaders. The implementation methods included lectures, discussions, question-and-answer sessions, pre- and post-tests of knowledge, weighing, measuring children’s height, and providing education on balanced nutrition, exclusive breastfeeding, nutritious complementary feeding, and clean and healthy living behaviors. The results showed a significant improvement in mothers’ knowledge about stunting, as reflected by the majority of participants (72%) having good understanding after the intervention. This program also motivated mothers to actively monitor their children’s growth and development at the integrated health posts (posyandu). The active participation of cadres and support from local authorities further strengthened the program’s success. In conclusion, empowering mothers of toddlers proved effective in increasing awareness of stunting prevention, supporting the creation of a healthy, smart, and stunting-free generation in Kampung Jawa. This program is recommended to be continued sustainably and serve as a model for similar interventions in other areas.